Context matters: A review of the determinant factors in the decision to adopt cloud computing in healthcare. (October 2019) - Gao, Fangjian; Sunyaev, Ali
Highlights: Diverse factors influence cloud computing adoption in healthcare. 124 factors for cloud computing adoption in healthcare have been identified. The identified factors fall in five conceptual categories. Industry-specific factors indicate two distinct characteristics. Abstract: Cloud computing is an IT service paradigm that can, if used meaningfully, enhance traditional health IT approaches and offer major benefits to the healthcare industry. However, its adoption by healthcare organizations has been accompanied by diverse challenges that could impede its meaningful use. Decisions about its adoption should be made after serious consideration of relevant industry-specific factors. Whereas the literature has focused on cloud computing adoption in general, the industrial specificities that influence the decision to adopt cloud computing in the healthcare context have yet to be systematically addressed. We reviewed empirical studies on both information systems and medical informatics to investigate the determinant factors of the cloud computing adoption decision in healthcare organizations and the industrial specificities of those factors. Based on the results of our review, we proposed a conceptual framework of cloud computing adoption studies in healthcare and made seven recommendations for related future research. Our research contributes to the theory by providing a comprehensive list of industry-specific factors that influence cloud computing adoption decisions in healthcare and explains their specificities for the healthcare industry. For practitioners, the identified factors serve as a checklist that informs healthcare organizations' decision making regarding cloud computing adoption.